Assessment of Mechanization Index of Sugarcane Cultivation in Mandya District, Karnataka, India - Aruna T N,; Bharath Kumar K,; Ramappa,; , Sachin C Hallad; Kavan Kumar V,; , Kishan Kumar; , Avesh Kumar Singh; Soumya Krishnan V, (Archives of Current Research International, 2024)
Farm mechanization is the development and introduction of mechanized assistance of all forms and at any level of sophistication in agricultural production to improve the efficiency of human time and labour. Mandya District is one of the most agriculturally prosperous districts in Karnataka. Sugarcane is the major commercial crop in the district. Farmers used to grow in all seasons. This study was carried out to assess the mechanization index in sugarcane cultivation in selected regions. Respondents from the selected region were selected randomly and collected information regarding types of machinery availability and usage in sugarcane cultivation. The overall mechanization index found 50.5 per cent in sugarcane cultivation in selected regions. The findings indicate that the process of laying seed beds had the highest mechanisation index (98.46 per cent), followed by irrigation (97.37 per cent) and weeding/spraying operations (57.81 per cent). Semi medium farmers found high mechanization index followed by medium, small and marginal farmers. The mechanization index was not uniform in selected region for all operations in sugarcane cultivation. Seedbed preparation found higher mechanization index followed by irrigation and weeding operation and zero per cent mechanization index for planting and harvesting operations of sugarcane. The results clearly depicted the importance of the farm mechanization in realizing additional profit to the farmers.